2009
DOI: 10.1097/sla.0b013e3181bcdaa7
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcome of Laparoscopic and Conventional Nissen Fundoplication

Abstract: CNF carries a higher risk for surgical reintervention compared with LNF, mainly due to incisional hernia corrections. The 10-year effectiveness of LNF and CNF is comparable in terms of improvement of GERD symptoms, PPI use, quality of life, and objective reflux control. Consequently, the long-term results from this trial lend level 1 support to the use of LNF as the surgical procedure of choice for GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(48 citation statements)
references
References 35 publications
2
42
1
3
Order By: Relevance
“…20, 22, 23 At 10 years, Broeders et al reported resolution or improvement of symptoms in 92.4% of patients. 24 Kelly et al also reported improvement in symptoms at 10 years using a visual analog scale. 27 The other 4 studies report satisfaction/cure rates from 84.9–100%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…20, 22, 23 At 10 years, Broeders et al reported resolution or improvement of symptoms in 92.4% of patients. 24 Kelly et al also reported improvement in symptoms at 10 years using a visual analog scale. 27 The other 4 studies report satisfaction/cure rates from 84.9–100%.…”
Section: Resultsmentioning
confidence: 97%
“…2023 PPI use at 1–3 years ranged from 5.5–16.7% and rose to 15–26.6% at 10 years. 19, 21, 22, 24, 25, 27 Three prospective cohort studies compared the effectiveness of LF between PPI responsive and non-responsive populations [Table 2]. 2830 All studies found symptom improvement in PPINR, though when compared to responders, symptom control was slightly lower.…”
Section: Resultsmentioning
confidence: 99%
“…GERD is a chronic disease and indications for surgery are an area of controversy, mainly because data concerning long-term efficacy are scanty [3]. Recently, 10-year follow-up studies showed high efficacy of laparoscopic antireflux surgery in terms of symptoms [22] and also acid reflux control [23] in patients with typical reflux symptoms responsive to PPI therapy. Currently, however, PPI-resistant heartburn/ regurgitation represent the most demanding clinical problem in GERD: it is the most common presentation of reflux syndromes in third referral gastrointestinal practices [2], and according to the American Gastroenterological Association, it should be considered the main indication for antireflux surgery [4].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies reported that after surgery there are subjects who will get worse or exacerbate dyspepsia-like symptoms (epigastric fullness, bloating, abdominal pain, flatulence), with worsening in GERD symptom control in up to 50% at long term follow-up[36,37]. …”
Section: Clinical Factors: Symptomsmentioning
confidence: 99%